Efeitos do Treino Cognitivo e educação em saúde sobre a cognição, sintomas depressivos e ansiosos em idosos com Comprometimento Cognitivo Leve - Casemiro, Francine Golghetto (Universidade Federal de São Carlos, 2017)
Introduction: With population aging, dementia has become one of the most relevant global public health problems. Among the different types, the one caused by Alzheimer's disease (AD) is the most frequent, accounting for almost 60% of the cases. It is believed that mild cognitive impairment (MCI) may be an initial symptomatic form of AD. The literature indicates that this group, despite the difficulties, has preserved the capacity to learn new information and adapt its behavior. Among the interventions in Gerontology, Health Education (HE) and Cognitive Training (CT) can be important choices for the improvement in cognition and associated factors as well as in the functional capacity of this population. Thus, it is imperative to develop studies, which use strategies of interventions for these elderly. Objective: Analyze the effects of CT and HE on cognition, depressive and anxious symptoms in elderly with CCL. Method: This is a randomized controlled trial. In order to analyze the improvement of the scores in the cognitive tests (ACE-R, MEEM), symptoms of depression and anxiety (Beck Scale) and memory complaint in the post-test we used Student's t test for paired samples. Results: The mean age of the Health Education Group (HEG) was 68 years (± 6.05), 70% of the participants were female, 80% were married, all were retired with an average of 4.9 (± 3.34) years of schooling. Already the Cognitive Training Group (CTG), 100% were female, mean age of 79.2 years (± 5.84), schooling 6.71 years (± 4.33), 71.4% widows and 71, 4% retired. As for the control group (CG), mean age was 77.3 (± 6.31) years, with schooling of 7 (± 4.53) years, 75% female, 58.3% married, and 91 , 7% retired. When comparing pre-test and post-test evaluations, HEG showed significant improvement in cognitive attention / orientation domains (p = 0.026), memory (p = 0.001), language (p = 0.033), and overall ACE score -R (p = 0.003). For CTG there was a significant improvement in the symptoms of depression (p = 0.00); (P = 0.004), memory (p = 0.000), overall ACE-R score (p = 0.000), and MMSE (p = 0.004). Regarding the CG, although an increase in the scores of the evaluations indicating improvement in the clinical picture was observed, this improvement was not significant. Therefore the conclusion is that the opportunities for intervention through workshops are important antecedents of evolutionary gains in old age, because they are believed to intensify social contacts, exchange of experiences and knowledge as well as personal improvement.
Effects of Cognitive Training and health education on cognition, depressive and anxious symptoms in elderly with Mild Cognitive Impairment
Keywords: Idoso; Intervenção; Comprometimento Cognitivo Leve; Gerontologia; Aged; Intervention; Mild Cognitive Impairment; Gerontology; CIENCIAS DA SAUDE::ENFERMAGEM